The diagnosis and management of fetal cardiac arrhythmias. (22nd April 2022) - Stott, Daniel; Pandya, Pranav P; Attilakos, George; Lang, Janet; Wolfenden, Joanne; Yates, Robert
Abstract : Key content: Fetal cardiac arrhythmias are relatively common and account for up to 20% of referrals to fetal cardiologists. Arrhythmias may occur because of structural abnormalities of the fetal heart, or because of abnormal functioning of the cardiac conduction system in an otherwise structurally normal heart. Arrhythmias may be diagnosed using ultrasound and M‐mode and Doppler echocardiography. Transplacental therapy for tachyarrhythmias has been one of the success stories of fetal cardiology, and good outcomes can be expected in the absence of hydrops. Congenital heart block is most commonly caused by the transplacental passage of anti‐Ro and anti‐La antibodies and transplacental therapy is less successful in managing this. Learning objectives: To enable clinicians to provide better counselling for patients about the prognosis of fetal arrhythmias. To learn how to diagnose fetal arrhythmias and know when to refer to a specialist centre if the diagnosis is suspected. To understand the treatment options available and the evidence‐based antenatal care schedule.